Perbedaan Self-Control berdasarkan Jenjang Sabuk, Gender dan Masa Latihan Pencak Silat pada Praktisi Beladiri - Muhamad Gilang Dharmawan; Kuston Sultoni; Finaldhi Palgunadhi (MAN Insan Cendekia Jambi, 2026)
Self-control is a fundamental psychological aspect relevant to the context of martial arts. Research on the factors that simultaneously influence it in pencak silat remains limited. This study aims to examine differences in self-control based on belt level, gender, and training duration among practitioners of pencak silat from the Persaudaraan Setia Hati Terate (PSHT). A quantitative approach with a comparative design and cross-sectional method was used in this study. The sample consisted of 62 active members of PSHT Sukasari in Bandung City, selected through purposive sampling. Self-control was measured using the 10-item Brief Self-Control Scale (BSCS), which covers the dimensions of inhibition and initiation. Data analysis was performed using one-way ANOVA and the independent samples t-test with the aid of SPSS 26.0. The results of the study showed significant differences based on belt level in the inhibition dimension (F = 2.790; p = .048; η² = 0.126), with the mori belt group achieving the highest mean score. Training duration showed significant differences in the inhibition dimension (F = 5.656; p = .002) and the initiation dimension (F = 3.179; p = .031), with a trend toward increased self-control as training duration increased. Gender did not show significant differences in either dimension (p > .05). It was concluded that the duration of training plays a more significant role in shaping the self-control of pencak silat practitioners than gender.